Digital revolution in Latin America beyond technologies - Gobbi, Maria Cristina [UNESP]; Filho, Francisco Machado [UNESP] (My University, 2015)
The challenge of interactive digital television (iDTV) in Latin America is to give opportunity of technological access and participation to a significant parcel of the population whose main information source is (still analog) television. The increase in connected device possession and system digitalization has been modifying consumption habits of audiovisual content. Television is still the home center, but now it divides the attention with mobile phones, smartphones, tablets and laptops, delineating a consumption that is multitasking, portable, mobile etc., but not always linked (independent devices use), there are multi-platform services and products that allow this interaction, though. Several externalities must be considered, either the different stages of digital signal development and application, or the cultural diversity, laws, technological unfolding, education, and even the economic aspects of each country. The paper aims to provide demands of how to digitally include these millions of citizens who don't have internet access.